Outcome of Fracture Shaft Humerus Treated with TENS - Manjunath, Dayanand; Shivanna, Deepak; Verma, Amit; Ramachandra; Nambiar, Rohan (International Journal of Orthopedics and Rehabilitation, 2017)
Introduction: Diaphyseal fractures of humerus accounts for 3% of all fractures. Though conservative treatment is popular it has its own limitations. Choice of surgical interventions ranges from plate osteosynthesis to Intramedullary nail that have their own merits and demerits. Hence a study was done to assess the outcome of treatment of Diaphyseal fractures of humerus treated by TENS nailing. Material and Methods: This is a prospective study of 20 adult patients with closed diaphyseal fracture of humerus treated with closed reduction and internal fixation with TENS nail between 2010 to 2013. Average follow up was 6 months. The fracture union was assessed clinically and radiologically. The functional result was evaluated with DASH scores. Results: Of the 20 cases that were treated 85 percent of them had fractures in the middle third. 60 percent of the fractures were transverse and 15 % were oblique. Majority of fracture (75 %) united in 10 weeks and 20% non union. The complications encountered in our series were non union in 4, Superficial infection in 2, 1 implant failure and stiffness of the elbow in 2 cases. 65 % of the patients had DASH Scoring in range of 10-30. Conclusion: Though nonunion rates are high. TENS provides relative stability but maintains the biological environment atthe fracture site which merits over open reduction. Its effectiveness in the oblique and spiral fractures where stability of reduction and compliance of the patient has a bigger role in the postoperative period is questionable.